Regulation of Histone Acetyltransferase TIP60 Function by Histone Deacetylase 3 - Yi, Jingjie (J Biol Chem, 2014)
The key member of the MOZ (monocyticleukaemia zinc finger protein), Ybf2/Sas3, Sas2, and TIP60 acetyltransferases family, Tat-interactive protein, 60 kD (TIP60), tightly modulates a wide array of cellular processes, including chromatin remodeling, gene transcription, apoptosis, DNA repair, and cell cycle arrest. The function of TIP60 can be regulated by SIRT1 through deacetylation. Here we found that TIP60 can also be functionally regulated by HDAC3. We identified six lysine residues as its autoacetylation sites. Mutagenesis of these lysines to arginines completely abolishes the autoacetylation of TIP60. Overexpression of HDAC3 increases TIP60 ubiquitination levels. However, unlike SIRT1, HDAC3 increased the half-life of TIP60. Further study found that HDAC3 colocalized with TIP60 both in the nucleus and the cytoplasm, which could be the reason why HDAC3 can stabilize TIP60. The deacetylation of TIP60 by both SIRT1 and HDAC3 reduces apoptosis induced by DNA damage. Knockdown of HDAC3 in cells increased TIP60 acetylation levels and increased apoptosis after DNA damage. Together, our findings provide a better understanding of TIP60 regulation mechanisms, which is a significant basis for further studies of its cellular functions.